A Red‐Light Azobenzene Di‐Maleimide Photoswitch: Pros and Cons. Issue 9 (13th July 2016) - Wu, Di; Dong, Mingxin; Collins, Catherine V.; Babalhavaeji, Amirhossein; Woolley, G. Andrew
Abstract : Azobenzene‐containing intramolecular cross‐linkers with maleimide functional groups (e.g., azobenzene di‐maleimide (ABDM)) have been used successfully for photocontrol of protein conformation and activity. However, the ABDM cross‐linker requires short wavelength UV light (340 nm) for photoisomerization, which is highly scattered and can be absorbed by biological materials. In addition, the maleimide functional groups of ABDM are expected to lead to a mixture of stereoisomeric products upon cross‐linking and these may undergo ring‐opening via hydrolysis. This study reports the design and synthesis of a tetra‐ ortho ‐methoxy substituted ABDM cross‐linker, which can be photoisomerized using red light (617 nm) and blue light (450 nm), thereby avoiding the use of UV. This new cross‐linker is used to cross‐link a peptide, 30ER that undergoes helix–coil transitions. As predicted, hydrolyzed succinimide cross‐linked products are observed by mass spectrometry. However, although, hydrolyzed products are present, and a mixture of stereoisomers presumably forms, photoisomerization of the cross‐linker nevertheless enables control of peptide helical conformation using red light. Thus, azobenzene di‐maleimides are practically useful, although chemically ill‐defined, photoswitchable cross‐linkers. Abstract : Design and synthesis of a tetra‐ ortho ‐methoxy substituted azobenzene di‐maleimide thiol‐reactive cross‐linker is reported. This molecule can cross‐link peptides and can be photoisomerized using red light (617 nm) and blue light (450 nm), thereby avoiding the use of UV.